Factors Influencing Treatment Default among Direct Observed Treatment Short-Course Enrolled in Pulmonary Tuberculosis - Kasim, Khadija S.; Aming-Hayudini, Magna Anissa E. (Future Science / FSH-PH Publications, 2022)
The Direct Observed Treatment Short course is a therapeutic intervention implemented by the government to treat patients infected with tuberculosis. But treatment default is still a problem that results to an increasing mortality rate among enrolled clients. This study aims to determine the factors influencing treatment default among DOTS enrolled pulmonary tuberculosis in Jolo RHU. The objectives of the study were the following: knew the socio-demographic factors influencing treatment default among pulmonary tuberculosis patient in terms of educational attainment, occupation, and family income, the treatment regimen related factors influencing the treatment default among pulmonary tuberculosis patient in terms of duration of treatment, problem with tablets, social/economic factors, adverse effect, and availability of medicine, and the significant relationship when grouped according to profile. The respondents involved in various occupations and were earning between 1000 and below and up to 3001 to 5000. This study utilized Inferential- evaluative research design. The Inferential was through correlational approach and quantitative techniques in the analysis and interpretation of data gathered. The study used descriptive statistics such as: frequency, percentage, and weighted mean as a tools of analysis of the data collected. The findings of the study revealed that most of the respondents’ educational attainment were at elementary level with 20 respondents having 66.66%, secondary level with 9 respondents having 30%, and vocational graduate of 1 respondent with 3.3%. However, the respondents show in their occupation that majority were from vendors of 20 respondents having 66.66%, followed by laborers of 4 respondents having 13.335, tricycle drivers of 2 respondents having 6.66%, construction workers of 2 respondents having 6.66%, fisherman with 1 respondent having 3.33%, and street sweeper having 1 respondent with 3.33%. Lastly, majority of the respondents earning P1,000 and below were the highest defaulters. 25 respondents having a family income of P1,000 and below showing 83.33%, only 5 respondents earning P3,001 to 5,000 family income which shows 16.66%, and none of them were earning P1,000 – 3,000. Likewise, it was revealed that the respondents were highly influenced by the statement that the treatment duration is too long. Likewise, the statement that too many tablets at a time and that the tablet is big has a high influenced on their treatment default. For Social/Economic Factors, they were moderately influenced on poor access to a DOTS facility to geographical factors and cultural belief limits the choice of treatment. They cannot decide however that post-disaster scenario influences treatment default among pulmonary tuberculosis patients. Also, the respondents were highly influenced with the experienced of orange colored urine, pain at the injection site, and hearing impairment. But they are moderately influenced with the experienced of skin allergy, flu-like symptoms, impairment of visual acuity, and burning sensation in the feet. On the availability of medicine, they are highly influenced that medicine is always available at the center. An average of 4.67 confirms that they were highly influenced to the problem with tablets. The average of 3.88 confirms they were moderately influenced with the social/economic factors. An average of 4.15 confirms that they were moderately influenced with adverse effect of the treatment regimen. The overall average of 4.24 means denotes that the respon]dents were moderately influenced with all the treatment regimen related factors influencing treatment default among Pulmonary Tuberculosis patients. Further, it was revealed in the result on the significant differences when the respondents were grouped in terms of profile resulted to L=.05, df=1 for numerator and df=16 for denominator, the F critical value is 4.49 therefore, the hypothesis is accepted and it was analyzed through ANOVA. Moreover, it was revealed that the result on the significant differences when respondents were grouped in terms of Educational Attainment, at α= .05, df=2 for numerator and df=27 for denominator, the F critical value is 6.49 therefore, the hypothesis is accepted. Result also revealed that on the significant differences when the respondents are grouped according to Occupation, at α=.05, df=5 for numerator and df=24 for denominator, the F critical value is 4.49 therefore, the hypothesis is accepted. In the same manner that the result on the significant differences when the respondents are grouped according to Income, at α= .05, df=5 for numerator and df=24 for denominator, the F critical value is 9.28 therefore, the hypothesis is accepted. Based on the findings of the study, it can be concluded that most of the pulmonary tuberculosis patient belong to the marginalized group of our society they only earn 1000 and below per month, in their early 30’s in age, and less educated. Since the treatment regimen related factors has no relationship with the treatment default among pulmonary tuberculosis patients, other factors not mentioned in the study could cause the treatment default. Profiles do not have relationship to the treatment default among pulmonary tuberculosis patients. The participants in this study have given the assurance of the ethical consideration. They were informed that this study will address them with highest respect of confidentiality and anonymity. It is also adhered that respondents were respected during the launching of the questionnaire. The following recommendations are forwarded based on the conclusions of the study that factors must be examined which may have triggered the treatment default among pulmonary tuberculosis patients. Future research on the topic must investigate the role of RHU’s in the treatment of pulmonary tuberculosis patient and the barangay health workers. Also an awareness seminar among the residents in their area of responsibility on the effect of defaulting treatment of pulmonary tuberculosis patient must conducted.